Refleksi Fenomena Judicialization of Politics pada Politik Hukum Pembentukan Mahkamah Konstitusi dan Putusan Mahkamah Konstitusi - Perwira, Indra (Jurnal Konstitusi, 2016)
This paper aimsÂ  toÂ  introduceÂ  theÂ  phenomenonÂ  ofÂ  judicializationÂ  ofÂ  politics in the treasury ofÂ  legalÂ  thoughtÂ  inÂ  Indonesia.Â  InÂ  addition,Â  thisÂ  paperÂ  alsoÂ  aims to reflect the presence of judicialization of politics in theÂ  ConstitutionalÂ  Court, either through legal policyÂ  onÂ  establishmentÂ  ofÂ  constitutionalÂ  courtÂ  orÂ  through its decisions. Theoretically, the phenomenon of judicialization of politics began to be known at the beginning of the 21st century characterized by the dependence of society to the court to resolve the issues related to morality, public policy, and political controversies. The presence of judicialization of politics can be reflected from the shift in the political settlement of the case which was originally made through political mechanisms to the settlement through a judicial mechanism. To see the phenomenon, this paper will explore the legal policy on establishment of the Constitutional Court. Through a historical perspective on the establishment, this paper would like to indicate that, in nature, the Constitutional Court is a political institution. In addition, this paper also analyzes the Constitutional Court decision in the case of judicial review on â€œPerpuâ€ of the Corruption Eradication Commission (KPK) and the decision regarding the dispute Election East Java province in 2008,Â  to show that the phenomenon of judicialization of politics has lived and practicedÂ  in the Constitutional Court as well.